1984
DOI: 10.1111/j.1365-2923.1984.tb01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of clinical performance of medical students: an integrative approach to evaluation

Abstract: Prediction of clinical performance of medical students in the clerkship phase was made possible in the earliest phase of medical education by a comprehensive and integrative evaluation instrument entitled 'Integrative Examination' (INTEX). A proportional sample of the content learned throughout the year is integrated for measuring knowledge, attitudes and skills on various cognitive levels within the clinical context of patient problems. INTEX was found to be a reliable instrument. Also it scores highly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The relationship of premedical grades to medical school grades has been reported in studies by Lipton et al (1984) and Rippey et al (1981). The studies of Murden et al (1978) and Benor & Hobfoll (1984) show that premedical school scores are more related to performance in the basic science courses than to clinical course performance. However, Wingard & Williamson (1973), in an extensive review of the literature, concluded that both pre‐academic and MCAT scores often reflect little more than ability to memorize isolated facts.…”
Section: Introductionmentioning
confidence: 92%
“…The relationship of premedical grades to medical school grades has been reported in studies by Lipton et al (1984) and Rippey et al (1981). The studies of Murden et al (1978) and Benor & Hobfoll (1984) show that premedical school scores are more related to performance in the basic science courses than to clinical course performance. However, Wingard & Williamson (1973), in an extensive review of the literature, concluded that both pre‐academic and MCAT scores often reflect little more than ability to memorize isolated facts.…”
Section: Introductionmentioning
confidence: 92%
“…This was in line with the attempts made at the Faculty of the Health Sciences at Ben-Gurion University to devise tests that better reflect students' knowledge and its openness and the willingness to adopt new evaluation methodologies for quality control (e.g. Benor & Hobful, 1984;Flynn & Reese, 1988) and for curricular decision making.…”
Section: The Course In Paediatric Surgery and Its Evaluationmentioning
confidence: 74%
“…Such course revision is in line with the attempts made at the Health Sciences at Ben-Gurion University to devise tests that better reflect students' knowledge (e.g. Benor & Hobful, 1984;Flynn & Reese, 1988). This is an example of the strengths, both potential and actual, of course evaluation that employs multiple knowledge dimensions obtained through cognitive mapping, which provides a sound basis for substantial decision making.…”
Section: Using the Evaluation In The Curriculum Revisionmentioning
confidence: 93%
“…At the Negev in Israel, very considerable attention has long been paid to both non‐cognitive criteria and biographical data, and life experience has been in particular focus (Benor & Hobfoll 1981). In this Issue , Shimon Glick reviews the Beer‐Sheva experience.…”
Section: Biographical Datamentioning
confidence: 99%